FAKTOR – FAKTOR PENDORONG DALAM PENYELESAIAN DELIMITASI ZEE ANTARA INDONESIA DAN FILIPINA - Aryastuti Dewi, Ni Made Yuni; Kumala Dewi, Putu Ratih; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT Delimitation problem between Indonesia and Philippines lasted for 20 years. The location of Indonesia boundaries ‘Miangas Island’ which is closer to the Philippines, becomes one of the key issues. This study will describe the factors that play a role in case resolution of ZEE delimitation between Indonesia and the Philippines. A country will strive to keep its outermost point. The debate over Indonesia's outer perimeter is seen from UNCLOS or Treaty of Paris 1898. However later in 2011 the Philippines agreed on UNCLOS understanding, and accepted Miangas Island as Indonesia's outermost point. This study was made for a change of attitude in the issue of ZEE delimitation settlement caused by several factors in it. This research will be descriptive qualitative research method and using the concept of determinant on foreign policy. Keywords : Miangas Island, Delimitation ZEE , Indonesia, Philippines.